Intracerebral sources of human auditory-evoked potentials - Picton, Terence W.; Alain, C.; Woods, D. L.; John, M. S.; Scherg, Michael; Valdes-Sosa, P.; Bosch-Bayard, J.; Trujillo, N. J. (Audiology & neurotology, 1999)
Evoked potentials to brief 1,000-Hz tones presented to either the left or the right ear were recorded from 30 electrodes arrayed over the head. These recordings were submitted to two different forms of source analysis: brain electric source analysis (BESA) and variable-resolution electromagnetic tomography (VARETA). Both analyses showed that the dominant intracerebral sources for the late auditory-evoked potentials (50-300 ms) were in the supratemporal plane and lateral temporal lobe contralateral to the ear of stimulation. The analyses also suggested the possibility of additional sources in the frontal lobes.
Gesehen am 22.03.2021